A general evaluation in aspects of internal diseases of the animals that were brought to the clinics of thıe veterinary facuıty of selçuk university in 1985- 1986 - Veysi ASLAN; Ali Muhtar TİFTİK (Eurasian Journal of Veterinary Sciences)
In this article an information was given about the types of diseases, the systems where they are located, their distribution based on the seasons and the animal species, the origines and the causes of diseases related to a total of 1060 animals that was brought to the clinics of the Veterinary Faculty Selçuk Üniversity in 1985- 1986. The distribution rate of diseases was found to be as 34.8% in horse, 16.2% in cow, 36.9% in calf, 6.2 % in sheep and 5.7% in cat and dog. In the region, the infections of the respiratory system were significantly higher. In fact, the tuberculosis, enzootic pneumonia, viral pneumonia and influenze were more common among these diseases. Furthermore several zoonotic diseases such as malleus and brucellosis, calf septisemia, parasitic disease and other disorders related to mineral and vitamin deficiency were also observed.